Bringing the Educational Reforms of the Cramton Report into the Case Method Classroom—Two Models - Gene R. Shreve (Washington University Law Quarterly, 1981)
This Article advocates that the Cramton Report's reforms' not be confined to the so-called "skills" courses but be considered with reference to all law school courses, including those employing the traditional case method approach.
Keywords: Case teaching method; Law schools; Legal education; United States; American Bar Association. Section of Legal Education and Admissions to the Bar